Supervisi Pendidikan Islam di Era Artificial Intelligence: Peluang dan Tantangan - Muhammad ‘Ainul Yaqin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Advances in artificial intelligence (AI) technology have brought about significant transformations in various sectors of life, including in the realm of education. In this context, the supervision of Islamic education as a mechanism for fostering and improving the quality of learning based on Islamic values, faces the demand to adapt to the development of technology. This article aims to explore the opportunities and challenges of Islamic education supervision in the AI era. On the one hand, AI offers various opportunities, such as optimizing learning monitoring, analyzing teacher performance data in real-time, and developing more personalized and adaptive learning models. But on the other hand, challenges also arise, including the potential reduction of spiritual values in the digitalization process, the gap in access to technology, and the need to improve digital literacy for Islamic educators and education supervisors. With a qualitative analysis approach and literature review, this article concludes that the integration of AI in Islamic education supervision must remain based on ethical principles and Islamic values, in order to be able to create a supervision system that is not only technologically efficient, but also spiritually and morally meaningful.